Ulysses, and the White Whale: Vittorio Gassman's Adaptation of Moby-Dick - Mariani, Giorgio (Dipartimento di Lingue e Letterature Straniere, Università degli studi di Verona, 2015)
At least since Cesare Pavese’s short but penetrating essays on Herman Melville, Italian critics and artists have been tempted to emphasize the latter’s greatness, and in particular the greatness of his masterpiece, Moby-Dick, by way of comparison with the accomplishments of the classic (European) literary tradition. Objecting to those who constructed American writers as inescapably “barbarous,” Pavese argued, “Melville is really a Greek. Read the European attempts to get away from literature and you feel more literary than ever, you feel small, cerebral, effeminate; read Melville, who was not ashamed to begin Moby-Dick with eight pages of citations (…) and your lungs are expanded, your brain is expanded, you feel more alive and more manly. And, as with the Greeks, no matter how dark the tragedy (Moby-Dick), so great are the tranquility and purity of its chorus (Ishmael) that we always leave the theater exalted in our own capacity for life” (57-58). One might say that Greek tragedy was Pavese’s way of bringing Melville, and Moby-Dick in particular, back to the Mediterranean, an intellectual maneuver somewhat replicated in the review of Pavese’s translation of Moby-Dick published by Elio Vittorini. Like Pavese, the Sicilian writer and critic refused to separate the “barbarian” from the “Greek” Melville, observing that what appears as barbarous and “primitive” in Moby-Dick is “in fact Homeric or Biblical” (127, my translation).